The influence of 5-HTTLPR transporter genotype on amygdala-subgenual anterior cingulate cortex connectivity in autism spectrum disorder. (April 2017) - Velasquez, Francisco; Wiggins, Jillian Lee; Mattson, Whitney I.; Martin, Donna M.; Lord, Catherine; Monk, Christopher S.
Abstract: Social deficits in autism spectrum disorder (ASD) are linked to amygdala functioning and functional connection between the amygdala and subgenual anterior cingulate cortex (sACC) is involved in the modulation of amygdala activity. Impairments in behavioral symptoms and amygdala activation and connectivity with the sACC seem to vary by serotonin transporter-linked polymorphic region (5-HTTLPR) variant genotype in diverse populations. The current preliminary investigation examines whether amygdala-sACC connectivity differs by 5-HTTLPR genotype and relates to social functioning in ASD. A sample of 108 children and adolescents (44 ASD) completed an fMRI face-processing task. Youth with ASD and low expressing 5-HTTLPR genotypes showed significantly greater connectivity than youth with ASD and higher expressing genotypes as well as typically developing (TD) individuals with both low and higher expressing genotypes, in the comparison of happy vs. baseline faces and happy vs. neutral faces. Moreover, individuals with ASD and higher expressing genotypes exhibit a negative relationship between amygdala-sACC connectivity and social dysfunction. Altered amygdala-sACC coupling based on 5-HTTLPR genotype may help explain some of the heterogeneity in neural and social function observed in ASD. This is the first ASD study to combine genetic polymorphism analyses and functional connectivity in the context of a social task.